2021
DOI: 10.1177/11206721211046718
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal fluocinolone acetonide implant for the treatment of persistent post-surgical cystoid macular edema in vitrectomized eyes

Abstract: Cystoid macular edema (CME) is the most common cause of decreased visual acuity after both vitrectomy and cataract surgery. Various strategies have been used for its treatment, such as intravitreal corticosteroids. The intravitreal fluocinolone acetonide implant (Iluvien®) is approved for the treatment of persisting diabetic macular edema and for the prevention of recurrence of non-infectious uveitis affecting the posterior segment. There are very few reports about its off-label use for post-surgical CME. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Miguel-Escuder et al reported four cases of PCME treated with FAc implant. Only one patient showed a suboptimal response to the treatment [5]. However, this patient underwent ERM peeling and intraocular lens fixation surgery 1 month after FAc implantation, probably causing an increase in inflammation.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Miguel-Escuder et al reported four cases of PCME treated with FAc implant. Only one patient showed a suboptimal response to the treatment [5]. However, this patient underwent ERM peeling and intraocular lens fixation surgery 1 month after FAc implantation, probably causing an increase in inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…While most cases of PCME resolve spontaneously, an important portion can be difficult to manage and significatively affect visual outcomes of PPV and other ocular procedures. The following sequential management strategy was proposed [6] However, drug clearance of topical treatment and IV anti-VEGF agents is faster in vitrectomized eyes, resulting in lower concentrations and limited efficacy [5,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations